Corn (Zea mays) growth in petroleum contaminated soil, remediated with orange (Citrus sinensis) peel extract - Marín Veláquez, Tomás Darío (Enfoque UTE, 2016)
Soil pollution has a strong impact when oil activity takes place within a savanna ecosystem. Any oil spill affects agricultural soils. Biostimulation with orange peel extract (Citrus sinensis) is an alternative for remediation of soil contaminated with crude oil and in this research the corn plant (Zea mays) was used as a biomarker of contamination level of a savanna soil after their treatment. Three samples of savannah soil contaminated with oil light crude were treated with dissolutions 1, 3 and 5% of extract of orange peel in water at a dose of 150 mL per kg of soil treated. The content of oils and fats was measured every 7 days, up to 42 days. Corn seeds were planted in soil samples, their growth was measured every 5 days for a period of 35 consecutive days, comparing their growth with seeds planted in a soil sample without contamination. According to an analysis of rank contrast, the plant growth was statistically the same in all samples up to 20 days; from there, evident differences regarding the pattern were shown.